2015
DOI: 10.1016/j.jet.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Should we regulate financial information?

Abstract: Regulations that require asset issuers to disclose payoff-relevant information to potential buyers sound like obvious measures to increase investor welfare. But in many cases, such regulations harm investors. In an equilibrium model, asset returns compensate investors for risk. By making payoffs less uncertain, disclosure reduces risk and therefore reduces return. As high-risk, high-return investments disappear, investor welfare falls. Of course, information is still valuable to each individual investor. But a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Any policies on financial disclosure or government communication failing to keep this point in mind may end up crowding out the idiosyncratic news and resulting in investment inefficiency. This policy implication fits broadly in line with the recent studies that speak to the dark side of financial disclosures or central bank communications (Di Maggio and Pagano, 2013, Kurlat and Veldkamp, 2013, Goldstein and Yang, 2014b. Theoretically, the endogenous overuse of information on the common shock due to multifirm cross learning results in an inefficient crowding-out effect on the use of information on the idiosyncratic shock.…”
Section: Overall Investment Efficiencysupporting
confidence: 84%
“…Any policies on financial disclosure or government communication failing to keep this point in mind may end up crowding out the idiosyncratic news and resulting in investment inefficiency. This policy implication fits broadly in line with the recent studies that speak to the dark side of financial disclosures or central bank communications (Di Maggio and Pagano, 2013, Kurlat and Veldkamp, 2013, Goldstein and Yang, 2014b. Theoretically, the endogenous overuse of information on the common shock due to multifirm cross learning results in an inefficient crowding-out effect on the use of information on the idiosyncratic shock.…”
Section: Overall Investment Efficiencysupporting
confidence: 84%
“…Brennan and Cao (1996) consider an economy with a risky asset with normally distributed payoff and a power derivative written on it. Other related works include Diamond and Verrecchia (1981), Marín and Rahi (2000), Vives (2008), and Kurlat and Veldkamp (2013). In contrast to the above literature, we allow for assets with more general payoff distributions, including derivative securities, and provide new results regarding price discovery in securities markets.…”
Section: Introductionmentioning
confidence: 99%
“…It is show that, when the second effect prevails, forcing the monopolist to disclose may lead to a Pareto inferior outcome. In contrast, in the production extension of Kurlat and Veldkamp [72], because the issuer is risk neutral, the Hirshleifer effect is absent, for information disclosure transfers risk from risk averse investors to a risk neutral issuer, which always contributes positively to welfare.…”
Section: Information Acquisition and Disclosurementioning
confidence: 95%
“…The tenth paper in the symposium by Kurlat and Veldkamp [72] addresses the question of whether disclosure of financial information should be regulated in the name of investor protection. It is found that mandatory disclosure may harm investors even when it improves the efficiency of decisions in the real sector.…”
Section: Information Acquisition and Disclosurementioning
confidence: 99%